2018
DOI: 10.1039/c7tb02912h
|View full text |Cite
|
Sign up to set email alerts
|

Stable DHLA–PEG capped PbS quantum dots: from synthesis to near-infrared biomedical imaging

Abstract: The short shelf-life of water-soluble quantum dots (QDs) due to colloidal instability represents a major drawback to their exploitation. This work examines the colloidal stability of PbS nanoparticles capped with dihydrolipoic acid–polyethylene glycol (DHLA–PEG) ligands terminated with functional groups such as –NH2, –COOH, OMe and –N3.\ud and their application for in vivo imaging. We prove a mechanism of colloidal instability and develop a strategy to produce for the first time stable PEG-capped PbS quantum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…However, these imaging modalities have limited spatial resolution and long scanning times. During the past 5 years, a number of reports on non-invasive brain imaging of mice in the 2nd NIR window have appeared using NIR nanoprobes such as SWNTs [31,98], QDs [34,41,[99][100][101][102], rare earth-doped nanomaterials [104,105], and organic dyes [65][66][67][68][69][70][71][72][73][74][75][76][77][104][105][106][107]. In 2014, Dai et al first reported 2nd NIR fluorescence imaging of a mouse brain by using (SWNTs) (Fig.…”
Section: Swnt Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these imaging modalities have limited spatial resolution and long scanning times. During the past 5 years, a number of reports on non-invasive brain imaging of mice in the 2nd NIR window have appeared using NIR nanoprobes such as SWNTs [31,98], QDs [34,41,[99][100][101][102], rare earth-doped nanomaterials [104,105], and organic dyes [65][66][67][68][69][70][71][72][73][74][75][76][77][104][105][106][107]. In 2014, Dai et al first reported 2nd NIR fluorescence imaging of a mouse brain by using (SWNTs) (Fig.…”
Section: Swnt Probesmentioning
confidence: 99%
“…In 2014, our group first reported the non-invasive fluorescence angiography of a mouse head using PbS/CdS QDs in the 2nd NIR window [34]. To date, several types of QDs including PbS QDs, Ag 2 S QDs, and InAs QDs have been used for brain imaging in the 2nd NIR window [100][101][102][103]. Figure 13.10 shows the fluorescence Reproduced from ref.…”
Section: Qd Probesmentioning
confidence: 99%
“…40,41 As both DHLA and DHLA-PEG are hydrophilic, the resultant QD@DHLA and QD@DHLA-PEG via the ligand exchange became water soluble. [42][43][44] Figure 5(b) shows the hydrodynamic diameters of the QD@DHLA and QD@DHLA-PEG measured by dynamic light scattering. The QD@DHLA had the mean hydrodynamic diameter of 5.5 nm, whereas the QD@DHLA-PEG exhibited the mean hydrodynamic diameter of $ 10 nm.…”
Section: -7mentioning
confidence: 99%
“…(e) Whole body and corresponding intensity surface, and ex vivo NIR fluorescence images of the liver (left inset) and spleen (right inset) of a mouse 24 h after tail vein injection of LNH 2 capped QDs. Reproduced with permission from (Figure3(a),[33] Copyright 2014 The American Chemical Society; Figure3(b),[32] Copyright 2010 The American Chemical Society; Figure3(c),[39] Copyright 2015 Wiley Publishing; Figure3(d),[38] Copyright 2015 The American Chemical Society; and Figure3(e),[45] Copyright 2018 RSC Publishing).…”
mentioning
confidence: 99%
“…the NIR range of low absorption of biological tissues (Figure3(e))[45]. Recently, PbS QDs were prepared in sizes between 2.4 and 3.2 nm using PbCl 2 , elemental S, dodecanethiol, and a toluene/oleylamine mixture at low temperatures[46].2.3.…”
mentioning
confidence: 99%